PELAKSANAAN MANAJEMEN K3 PADA PT ADYAWINSA T & E DI JAKARTA - Maya Sofiana (Majalah Ilmiah Bijak, 2017)
This writing aims to know how to implement of Occupational safety and health (OHS)  management, obstacles, and solutions on PT Adyawinsa Telecommunication & Electrical. This writing is executed on PT Adyawinsa Telecommunication & Electrical, with the methods of literature writing, observation, and interviews.The results of this writing is represent that, implement of Occupational safety and health management (OHS) is still not suitable because it is still in development stage, so less than the maximum in the application of plicies and procedures of OHS.The implemetation of OHS is the determination of OHS policy, the implementation of OHS wich consists of inspectionOHS and awareness raising program of OHS, and monitoring  and evaluation of OHS.The constraints faced is implement of Occupational safety and health management (OHS) is difficult to make changes in the implementation of OHS, lack of undersatanding and awareness of employees to risk in the work environtment, lack of basic understanding measurement inspection ofOHS,”safety talk” is difficult is difficult for employees who are in site/DOP, lack of understanding ofOHS  procedures, training modules, and difficulty adjustment schedule of leaderThe solutions in facing is implement of Occupational safety and health management (OHS) is the required awareness and support of the implementation of the OHS for all parties, the importance of APD socialization, make clear basic mesurement/standard for inspection OHS, safety talk is done via email for empoyee who is in site/DOP, the importance of understanding of OHS procedure before disseminating, preparing more training modules and making management review and review schedule a year ahead.